Dynamic analysis of high-speed railway bridge decks using generalised beam theory. (May 2017) - Bebiano, R.; Calçada, R.; Camotim, D.; Silvestre, N.
Abstract: This paper presents the details and illustrates the application of a semi-analytical Generalised Beam Theory (GBT) formulation for the dynamic analysis of high-speed railway bridge decks. The technique, which takes into account the cross-section local/distortional and shear deformations, provides an original "doubly modal" representation of the dynamic response, which makes it possible to acquire deep insight into the mechanics of the deck structural behaviour. It is employed to investigate the dynamic behaviour of a real high-speed railway viaduct, comprising a series of identical 46 m -span simply supported box girder pre-stressed concrete decks carrying two tracks – the augmented structural response associated with resonance due to the crossing of trains at high-speeds is captured. The results obtained provide evidence that local/distortional deformation can play a significant role on the dynamic response of such structures. Moreover, the GBT analyses, whose validity is confirmed through the comparison with values yielded by shell finite element analyses, are shown to provide accurate results while involving just a few degrees of freedom. Highlights: Semi-analytical GBT formulation for the dynamic analysis of high-speed railway bridge decks developed. Original "doubly modal" representation of the solution (deformation and vibration modes). Response of a pre-stressed concrete box girder deck investigated (real and HSLM high-speed trains). Results show that local/shear deformation plays a relevant role in the response at resonance. GBT analyses are significantly more efficient that shell finite elements (fewer d.o.f. and structural clarity).